Pengaruh Pengungkapan Environmental, Social, Governance (ESG) dan Profitabilitas Terhadap Return Saham Perusahaan Indeks IDX30 - Nadila Eka Apriyanti; Nina Febriana Dosinta; Fera Damayanti (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to analyze the effect of Environmental, Social, Governance (ESG) disclosure and profitability on stock returns in IDX30 index companies for the 2022–2024 period. This study uses a quantitative method with secondary data obtained from annual reports, sustainability reports, and stock price data taken from the Yahoo Finance website. The research sample was selected using a purposive sampling technique, resulting in 26 companies with a total of 78 observational data. Data analysis used panel data regression with the help of EViews 12 software. The results show that environmental disclosure (coefficient = 0.734; prob = 0.0081), social (coefficient = 1.072; prob = 0.0015), governance (coefficient = 0.657; prob = 0.0048), and profitability (coefficient = 3.660; prob = 0.0000) have a positive effect on stock returns. These results indicate that investors are starting to consider financial and non-financial information in making investment decisions to assess a company's prospects and sustainability. This study expands the empirical evidence on the influence of ESG and profitability on stock returns by testing the influence of each ESG dimension separately, namely environmental, social, and governance, thus providing a more specific analysis of the influence of each ESG dimension on stock returns.